Visual and patient reported outcomes provided by a refractive multifocal intraocular lens based on continuous transitional focus - Jorge L. Alió; Antonio Martínez-Abad; Ramón Ruiz-Mesa; Hyo Myung Kim; Javier Mendicute; Filomena J. Ribeiro; Mike P. Holzer; Mario Cantó-Cerdán (Eye and Vision, 2024)
Abstract Purpose To analyze the quality of vision of patients implanted bilaterally with the multifocal Precizon Presbyopic intraocular lens (IOL), as well as to evaluate the visual performance provided by the lens. Setting Vissum Miranza Alicante. Design Prospective multicenter study. Methods 56 patients (mean age 65.0 ± 8.7 years old) underwent bilateral implantation with multifocal Precizon Presbyopic IOL. The quality of vision was assessed by a quality of vision questionnaire at 6 months after the implantation procedure, a complete eye examination was also performed including visual and refractive measurements, defocus curve and contrast sensitivity assessment. Visual and refractive variables were compared in preoperative, 3-month postoperative and 6-month postoperative visits by Wilcoxon test. Results The quality of vision analysis showed the absence of severe glare and severe haloes in all evaluated patients. Likewise, non-symptoms of glare, haloes and starbursts were seen in 75%, 68%, and 55% of subjects, respectively. Efficacy and safety index was 1.26 and 1.42, respectively. The 6-month postoperative binocular uncorrected distance visual acuity and near uncorrected visual acuity were 0.00 ± 0.09 and 0.20 ± 0.13 logMAR, respectively. Mean spherical equivalent was 0.29 ± 0.45 D. Conclusions The Precizon Presbyopic NVA IOL (OPHTEC BV) provides a suitable quality of vision with a low rate of disturbance photic phenomena induction, as well as an excellent visual performance at main distances of sight accomplishing the visual demands of the majority of patients.